Pelaksanaan Teknik Hypnotherapy (Terapi Dengan Hipnosis) Dalam Pencegahan Masalah Pada Anak Usia Dini - Yusnika Damayanti; Jukarnain Jukarnain; Rizki Amalia; Nunung Suryana Jamin; Leli Leli; Rizki Andita Noviar; M. Khalid Fredy Saputra (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Hypnoparenting is a program for parents who want to educate their children in a more effective way or technique, including how to "control" and build children's mentality with hypnosis. The purpose of PkM is to increase parents' knowledge and insight in educating children by implementing good parenting patterns. For teachers, it can increase knowledge to apply in providing teaching to students. The method used in PkM activities is socialization and Mentoring Discussion Questions and Answers about the implementation of hypnotherapy techniques (therapy with hypnosis) in preventing problems in early childhood, the correct parenting patterns. The results of community service, namely the questionnaire assessment, show that the parenting patterns of students' parents in Mendabe Village/Kindergarten for the good category are 46% while the category is not good 53%. This condition is because many parents do not know how to provide the right parenting patterns for their children. The conclusion of this activity is that parental knowledge has improved with the socialization and mentoring of the implementation of hypnotherapy techniques (therapy with hypnosis) in preventing problems in early childhood.